A simple analytical method for heterogeneity corrections in low dose rate prostate brachytherapy. (29th June 2015) - Hueso-González, Fernando; Vijande, Javier; Ballester, Facundo; Perez-Calatayud, Jose; Siebert, Frank-André
Abstract: In low energy brachytherapy, the presence of tissue heterogeneities contributes significantly to the discrepancies observed between treatment plan and delivered dose. In this work, we present a simplified analytical dose calculation algorithm for heterogeneous tissue. We compare it with Monte Carlo computations and assess its suitability for integration in clinical treatment planning systems. The algorithm, named as RayStretch, is based on the classic equivalent path length method and TG-43 reference data. Analytical and Monte Carlo dose calculations using Penelope2008 are compared for a benchmark case: a prostate patient with calcifications. The results show a remarkable agreement between simulation and algorithm, the latter having, in addition, a high calculation speed. The proposed analytical model is compatible with clinical real-time treatment planning systems based on TG-43 consensus datasets for improving dose calculation and treatment quality in heterogeneous tissue. Moreover, the algorithm is applicable for any type of heterogeneities.